(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2020)
The financial enquiry of human trafficking crime is increasingly gaining bigger relevance. It may constitute a specific crime as money laundering or a tax evasion crime, may allow accessory measures as seizure and outline conclusive circumstantial evidence, ratifying victim’s testimony and ensuring in this manner the consequent conviction. In this paper, in addition to give some general rules about the concept and importance of financial enquiry, the differences of funding between human trafficking and illegal immigration will be examined as well as the factors the Courts are taking into account in the financial sphere to bring credibility to victim’s testimony.